Infantile granular parakeratosis: Case report and review of the literature - Hanan M Almeshal (Wolters Kluwer Medknow Publications, 2020)
Granular parakeratosis (GP) is a benign skin disease that has been reported in adults and children. Lesions usually affect the axillae, groin, and submammary region. The primary lesions present as brown keratotic papules and can form plaques. The etiologies implicated in the development of GP include the use of topical cream and the use of deodorants, local irritation and in children, it was linked to repetitive washing of the affected area and the use of zinc oxide cream. This is a case report of GP in a 14-month-old boy noted after washing the groin area with soap and using zinc oxide cream. The lesions have improved after the discontinuation of the use of zinc oxide cream and soap in washing the affected area.